(untitled) (Revista Contexto & Saúde, 2025)
This study aimed to investigate the relationship between air quality in the municipalities of Canoas and Esteio/RS and reported cases of COVID-19 from March 1, 2020 to February 28, 2021. The analysis was realized by searching and relating air quality data for NO 2 , SO 2 , MP 10 and MP 2.5 obtained from the database of the Fundação Estadual de Proteção Ambiental Henrique Luis Roessler- RS (FEPAM) and data from patients reported with COVID-19 provided by the Federal Government. A prevalence of patients infected by COVID-19 in females (54%) between 30 and 39 years old (23%) was observed in both municipalities. The most listed symptoms were dyspnea (83%) and sore throat (74%) and the most common comorbidities presented by infected patients were asthma (5.37%) in Canoas and Chronic Heart Disease (6.17%) in Esteio. The pollutant values analyzed showed fluctuations and even exceeded the established limits, and a positive statistic (<0.001) was observed between the SO2 levels and the number of confirmed cases of COVID-19 in the evaluated municipalities. With the results showing the positive relationship between air quality and COVID-19 cases, it’s expected to be able to contribute to the development of public policies that improve air quality and reduce the damage they cause to human health, as well as educational and preventive measures to increase awareness among the general population about the importance of air quality.